'Like it, don't like it, you have to like it': children's emotional responses to the absence of transnational migrant parents in Lombok, Indonesia. Issue 6 (2nd November 2018) - Beazley, Harriot; Butt, Leslie; Ball, Jessica
ABSTRACT: This article explores the experiences and emotions of children in rural East Lombok, Indonesia, who stay behind with relatives or neighbours while their parents leave the country for work. The article contributes to recent scholarship of children's experiences of transnational migration in Southeast Asia by drawing out the complex emotions of children who stay behind. Based on research conducted in four 'sending' villages, the article describes children's lived experiences of their parent's transnational migration, and their intense feelings that whether they 'like it or don't like it', they have no choice but to acquiesce to their parents' long, often indeterminate absences. The research suggests that stay-behind children are entangled in community anxieties pervading the emotional economy of transnational migration, including the embodied emotion of shame ( malu ) which shapes children's responses to parental absence. By focusing on children's own views and experiences, we contribute to growing debates about the implications of migration for children's rights and well-being in Southeast Asia.